Blockchain in maritime cybersecurity - Pitkänen, Emilia (My University, 2021)
Blockchain technologies can be used for many different purposes from handling large amounts of data to creating better solutions for privacy protection, user authentication and a tamper proof ledger which lead to growing interest among industries. Smart contracts, fog nodes and different consensus methods create a scalable environment to secure multi-party connections with equal trust of participanting nodes’ identity. Different blockchains have multiple options for methodologies to use in different environments. This thesis has focused on Ethereum based open-source solutions that fit the remote pilotage environment the best. Autonomous vehicular networks and remote operatable devices have been a popular research topic in the last few years. Remote pilotage in maritime environment is persumed to reach its full potential with fully autonomous vessels in ten years which makes the topic interesting for all researchers. However cybersecurity in these environments is especially important because incidents can lead to financial loss, reputational damage, loss of customer and industry trust and environmental damage. These complex environments also have multiple attack vectors because of the systems wireless nature. Denial-of-service (DoS), man-in-the-middle (MITM), message or executable code injection, authentication tampering and GPS spoofing are one of the most usual attacks against large IoT systems. This is why blockchain can be used for creating a tamper proof environment with no single point-of-failure. After extensive research about best performing blockchain technologies Ethereum seemed the most preferable for decentralised maritime environment. In comparison to most of 2021 blockchain technologies that have focused on financial industries and cryptocurrencies, Ethereum has focused on decentralizing applications within many different industries. This thesis provides three Ethereum based blockchain protocol solutions and one operating system for these protocols. All have different features that add to the base blockchain technology but after extensive comparison two of these protocols perform better in means of concurrency and privacy. Hyperledger Fabric and Quorum provide many ways of tackling privacy, concurrency and parallel execution issues with consistent high throughput levels. However Hyperledger Fabric has far better throughput and concurrency management. This makes the solution of Firefly operating system with Hyperledger Fabric blockchain protocol the most preferable solution in complex remote pilotage fairway environment.
Keywords: blockchain, maritime cybersecurity, Ethereum, IoT, cyber threats, smart contracts, fog nodes, permissioned blockchain networks, Quorum, Hyperledger Fabric, Corda, Firefly